Low Cost Housing Using Innovative And Advanced Techniques - Bhalerao Rupali Alish; Gite Kalyani Dilip; Jadhav Shital Rajabapu; Sathe Hema Sunil (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Housing is a basic social need where families can have a comfortable living and work in a sustainable environment. To stay healthy one need a proper place to reside for the entire life and that is home. This is one important component of one's life. But contrary to this, in India type and number of homes available is not adequate as per the estimation reported by the Ministry of Housing and Urban Poverty Alleviation, Government of India. Our country is developing country, and to transform it into developed country the main thing that will help is infrastructural development. Providing housing facility to the low income group people will help our country for the development. But as we know that for building a simple house cost involved is very high; and this will not be affordable for people, so that government had laid no. of schemes; so that everyone will have a comfortable house. But it is observed that funds provided under this scheme are not sufficient; so that there is need to develop the new techniques; which will reduce the cost but will give same strength as per conventional methods. This paper is focusing on the materials and methods of construction; which will provide effective and economical housing facility.